The Role of Non-Governmental Organizations in Public Diplomacy - Kalinov, Kalin (Media and Language, 2021)
One of the key debates in the field of public diplomacy in recent years relates to the positioning of non-governmental organizations within the existing paradigm. Most authors defend one of two completely opposite points of view. For some researchers the NGOs are in a position to participate equally and defend policies on their own, while others support their conceptualization as a tool for communication with a particular audience segment. The present research aims to present the two theoretical viewpoints in detail as well as the points of collision between them. Subsequently, possible directions for future empirical research are outlined, which could define the role of the NGOs in contemporary public diplomacy in a clearer manner. The present article is part of the project “Dimensions and Transformations of the Digital Public Diplomacy: Defining the Field, Communication Channels, Stakeholders and Measuring Effectiveness”, financed by the National programme “Young Scholars and Postdoctoral Students” 2021.